(untitled) (VERITAS LEGIS JOURNAL, 2026)
Risks in social legislation constitute fundamental criteria for the formation of constitutional legal guarantees and regulatory classifications. In April 2023, the Republic of Kazakhstan adopted the Social Code of the Republic of Kazakhstan, which for the first time at the legislative level introduced a conceptual definition of “social risk” by listing certain legal facts that form its basis. However, the list provided by this codified regulatory legal act is rather limited. It does not take into account many provisions that are not regulated by this Code, as well as those governed by other legislative acts or norms of international law. In addition, it contains certain legal norms that fall under the characteristics of a “defective legal norm” or legal casuistry. The purpose of this article is to present a scientific and analytical study of the legal category of “social risks” in theoretical, regulatory, and law-enforcement contexts. In the course of the study, the author aims to address the following objectives: to determine the substantive evaluative significance of the legal category under consideration; to present a concise classification of social risks based on their fundamental purpose and semantic nature; and to analyze certain “defective” legal norms contained in the national legislation in order to identify the factors and extent of their impact on the stability and security of the Republic of Kazakhstan. The author proposes specific legal revisions and amendments aimed at correcting the analyzed casuistic regulators and sources of law. The conclusion of the article presents the results of the conducted scientific legal research.